2019
DOI: 10.1007/s11135-019-00851-3
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative model for the spread of online information

Abstract: This paper quantifies the spreading speed, scale and influence of online information. Based on the epidemic Susceptible-Infected-Removed (SIR) model, we propose a piecewise SIR model to study the problem of information spreading in online social networks. In the model, we propose that the recovery rate of spreaders should be a piecewise function rather than a constant. Only in this way can the model reveal the different roles of online spreaders in different spreading periods. Based on this piecewise recovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Zhao et al introduced the SI communication model focused on emergent blog topics. The study investigates the pattern of public opinion dissemination in emergent scenarios without considering the influence of the removers [44]. And Dong et al used the SEIR model to study the rumor spreading process of Facebook [33].…”
Section: Information Dissemination Modelmentioning
confidence: 99%
“…Zhao et al introduced the SI communication model focused on emergent blog topics. The study investigates the pattern of public opinion dissemination in emergent scenarios without considering the influence of the removers [44]. And Dong et al used the SEIR model to study the rumor spreading process of Facebook [33].…”
Section: Information Dissemination Modelmentioning
confidence: 99%
“…The results showed that the application of random or directed immunity could effectively prevent the diffusion of rumors while reducing the credibility of rumors. Jiang and Yan ( 3 ) proposed a piecewise SIR model to quantify the diffusing speed, scale and influence of online information. The simulation results showed that there was no proportional relationship between the sustained influence of a message and the number of diffusers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The epidemiology-based models (in particular SIR) are also used to study CP, which succeed to capture saturation (e.g., [12]- [14]). The current and total copies are respectively modelled as infected and (infected+recovered) populations.…”
Section: Related Workmentioning
confidence: 99%